PENGARUH MODEL PEMBELAJARAN AKTIF DENGAN PERMAINAN BOLA GULING TERHADAP HASIL BELAJAR SISWA SMA - Nugrahantia, Ayu; Soeprodio, Soeprodio; Kadarwati, Sri (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2011)
This study is aimed to investigate the influence of active learning with college ball game and magnitude of impact on student learning outcomes. A preliminary study conducted in SMA 11 Semarang indicated that students learning outcomes on buffer solution and hydrolysis topic are low. This is indicated by the value of daily tests or the last five years thats unable to reach a predetermined value, which is 65. A preliminary study also showed that the level of understanding and interesting in students learning is still lacking. This problem requires an appropriate teaming model to attract the attention of students in learning. Therefore, the active learning model with a college ball game was applied, and then impact on student learning outcome was studied. The population in this study was students of class XI IPA of SMA 11 Semarang on 200912010 academic year. Experimental design used is post-test only control group design and cluster random sampling methode. Based on the analysis of two average difference test is was obtained that the value tcatt (3.92)> ttabte (1.67). It can be concluded that there are differences in learning outcomes between the two groups. The results by test analysis biserial of correlation showed that (rb) (0.53)> SErb*1.96 (0.29). It can be concluded that the correlation between two variables is reliable. The results showed that active learning with college ball game contributes to students learning outcomes with the contribution of 28. 28%.